PENERAPAN METODE KOMBINASI JIGSAW DAN CONCEPT MAPPING MENINGKATKAN PRESTASI BELAJAR TENTANG KEBUTUHAN IBU HAMIL - Nurohmah, Norma; Tarawan, Vita M; Purba, Ambrosius (Universitas Tribhuwana Tunggadewi, 2020)
The learning model is one of the external factors that affect motivation and learning achievement. Use of learning models that are not in accordance with the material will become obstacles in achieving objectives and less effective and efficient learning. The purpose of this study is to analyze the Influence combination jigsaw method and concept mapping on learning motivation in students. The method used is quantitative method with quasi-experimental design using a crossover design of this study means to intervene in the two groups with the same treatment at a time when different. The number of study participants as many as 64 people. Research shows students in both groups learning methods learning motivation scores on the learning method was higher (p